A Novel Tetramethylpyrazine Derivative Prophylactically Protects against Glutamate-Induced Excitotoxicity in Primary Neurons through the Blockage of N-Methyl-D-aspartate Receptor - Hu, Shengquan; Hu, Huihui; Mak, Shinghung; Cui, Guozhen; Lee, Mingyuen; Shan, Luchen; Wang, Yuqiang; Lin, Huangquan; Zhang, Zaijun; Han, Yifan (Frontiers in Pharmacology, 2018)
The over-activation of NMDA receptor via the excessive glutamate is believed to one of the most causal factors associated with Alzheimer’s disease (AD), a progressive neurodegenerative brain disorder. Molecules that could protect against glutamate-induced neurotoxicity may hold therapeutic values for treating AD. Herein, the neuroprotective mechanisms of dimeric DT-010, a novel derivative of naturally occurring danshensu and tetramethylpyrazine, were investigated using primary rat cerebellar granule neurons (CGNs) and hippocampal neurons. It was found that DT-010 (3-30 µM) markedly prevented excitotoxicity of CGNs caused by glutamate, as evidenced by the promotion of neuronal viability as well as the reversal of abnormal morphological changes. While its parent molecules did not show any protective effects even when their concentration reached 50 µM. Additionally, DT-010 almost fully blocked intracellular accumulation of reactive oxygen species caused by glutamate and exogenous oxidative stimulus. Moreover, Western blot results demonstrated that DT-010 remarkably attenuated the inhibition of pro-survival PI3K/Akt/GSK3β pathway caused by glutamate. Ca2+ imaging with Fluo-4 fluorescence analysis further revealed that DT-010 greatly declined glutamate-induced increase in intracellular Ca2+. Most importantly, with the use of whole-cell patch clamp electrophysiology, DT-010 directly inhibited NMDA-activated whole-cell currents in primary hippocampal neurons. Molecular docking simulation analysis further revealed a possible binding mode that inhibited NMDA receptor at the ion channel, showing that DT-010 favorably binds to Asn602 of NMDA receptor via arene hydrogen bond. These results suggest that DT-010 could be served as a novel NMDA receptor antagonist and protect against glutamate-induced excitotoxicity from blocking the upstream NMDA receptors to the subsequent Ca2+ influx and to the downstream GSK3β cascade. Keywords Alzheimer’s disease, tetramethylpyrazine derivative, NMDA receptor, neuroprotection, oxidative stress, GSK3β